Experimental investigation of single media thermocline storage with eccentrically mounted vertical porous flow distributor. (1st March 2018) - Gajbhiye, Pravin; Salunkhe, Nikhil; Kedare, Shireesh; Bose, Manaswita
Graphical abstract: Highlights: A new design of single media thermal storage tank with a flow distributor is proposed. Thermocline thickness for the charging cycle is analysed experimentally. Smaller thermocline thickness compared to the dual media tanks is obtained. Abstract: This paper provides an experimental analysis of a single media thermocline storage system equipped with a perforated, eccentrically mounted, vertical and porous flow distributor. The eccentrically mounted vertical porous flow distributor allows the fluid to ooze according to the matching density. Thermocline formation and propagation during the charging cycle are analysed through multiple sets of experiments for different flow rates. It is observed that thermocline layer is thinner for higher flow rates. Lower diffusion rate at higher Peclet number leads to thinner thermocline layer. The results obtained are useful for validation and design of single tank thermocline systems. Also, it provides guidelines for flow control and operation of the charging cycle.